Research on the Cooperative Mechanism of Administrative Law Enforcement and Supervision in the Stage of Compulsory Education - Yingyi Wang; Mohd Asri bin Mohd Noor (Journal of Advanced Research in Education, 2025)
Against the backdrop of the Chinese government’s advocacy for establishing a collaborative mechanism between educational administrative law enforcement and educational supervision, this article examines the current state of these two domains. The study identifies several issues, including ambiguous responsibilities, mutual buck-passing, and a lack of coordination. The author argues that it is essential to clarify the concepts of educational administrative law enforcement and educational supervision at the compulsory education stage and to delineate the relationship between them. This clarity is crucial for constructing an effective collaborative mechanism for educational administrative law enforcement and supervision at the basic education stage.